Fungal aryl-alcohol oxidase: a peroxide-producing flavoenzyme involved in lignin degradation - Hernández-Ortega, Aitor; Ferreira, Patricia; Martínez, Angel T. (Applied microbiology and biotechnology, 2012)
Aryl-alcohol oxidase (AAO) is an extracellular flavoprotein providing the H 2 O 2 required by ligninolytic peroxidases for fungal degradation of lignin, the key step for carbon recycling in land ecosystems. O 2 activation by Pleurotus eryngii AAO takes place during the redox-cycling of p- methoxylated benzylic metabolites secreted by the fungus. Only Pleurotus AAO sequences were available for years, but the number strongly increased recently due to sequencing of different basidiomycete genomes, and a comparison of 112 GMC (glucose–methanol–choline oxidase) superfamily sequences including 40 AAOs is presented. As shown by kinetic isotope effects, alcohol oxidation by AAO is produced by hydride transfer to the flavin, and hydroxyl proton transfer to a base. Moreover, site-directed mutagenesis studies showed that His502 activates the alcohol substrate by proton abstraction, and this result was extended to other GMC oxidoreductases where the nature of the base was under discussion. However, in contrast with that proposed for GMC oxidoreductases, the two transfers are not stepwise but concerted. Alcohol docking at the buried AAO active site resulted in only one catalytically relevant position for concerted transfer, with the pro- R α-hydrogen at distance for hydride abstraction. The expected hydride-transfer stereoselectivity was demonstrated, for the first time in a GMC oxidoreductase, by using the (R) and (S) enantiomers of α-deuterated p -methoxybenzyl alcohol. Other largely unexplained aspects of AAO catalysis (such as the unexpected specificity on substituted aldehydes) can also be explained in the light of the recent results. Finally, the biotechnological interest of AAO in flavor production is extended by its potential in production of chiral compounds taking advantage from the above-described stereoselectivity.